2008
DOI: 10.1007/s10584-008-9475-0
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation drives interannual variation in summer soil respiration in a Mediterranean-climate, mixed-conifer forest

Abstract: Predictions of future climate change rely on models of how both environmental conditions and disturbance impact carbon cycling at various temporal and spatial scales. Few multi-year studies, however, have examined how carbon efflux is affected by the interaction of disturbance and interannual climate variation. We measured daytime soil respiration (R s ) over five summers (June-September) in a Sierra Nevada mixed-conifer forest on undisturbed plots and plots manipulated with thinning, burning and their combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…The two large variations of annual R S were both ascribed to changes in SWC. Large interannual variations of R S were also observed in a beech forest (Epron et al 2004), broadleaf forests (Martin and Bolstad 2005), and a Mediterranean forest (Asensio et al 2007;Concilio et al 2009). R S in a humid year was twice as high as in a dry year in a Mediterranean holm oak forest (Asensio et al 2007).…”
Section: Interannual Variation Of Soil Respiration and Its Controllinmentioning
confidence: 87%
See 3 more Smart Citations
“…The two large variations of annual R S were both ascribed to changes in SWC. Large interannual variations of R S were also observed in a beech forest (Epron et al 2004), broadleaf forests (Martin and Bolstad 2005), and a Mediterranean forest (Asensio et al 2007;Concilio et al 2009). R S in a humid year was twice as high as in a dry year in a Mediterranean holm oak forest (Asensio et al 2007).…”
Section: Interannual Variation Of Soil Respiration and Its Controllinmentioning
confidence: 87%
“…The changes of annual mean SWC can be influenced by precipitation and ET. Variation in precipitation amount usually explains interannual variability in SWC, which subsequently influences annual R S as in a temperate forest (Borken et al 1999(Borken et al , 2006, within seasonally dry biomes (savannas, shrublands, and deserts) (Raich et al 2002), in a Hesse forest (Epron et al 2004), and a Mediterranean forest (Concilio et al 2009). However, in this study, we found that SWC had no relation with precipitation amount but had a tight relation with rainfall frequency (Fig.…”
Section: Interannual Variation Of Soil Respiration and Its Controllinmentioning
confidence: 99%
See 2 more Smart Citations
“…Ecosystems in arid and semi-arid regions are sensitive to changes in climate [1][2][3][4][5]. Recently, a significant increase in vegetation growth and a change in climate have been observed in Xinjiang, a typical arid and semi-arid ecosystem located in Northwest China [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%